2004
DOI: 10.1016/j.jvs.2003.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Combined l-arginine and antioxidative vitamin treatment mollifies ischemia-reperfusion injury of skeletal muscle

Abstract: Enhanced production of superoxide in L-arginine-depleted environments and concomitant reduction of nitric oxide (NO) concentration are involved in ischemia-reperfusion (I/R) injury. Treatment with L-arginine or antioxidative vitamins alone and in combination was used to mollify I/R injury in skeletal muscle. Untreated rabbits were compared with those treated with L-arginine/antioxidative vitamin cocktail Omnibionta only, or a combination of L-arginine/ antioxidative vitamins during hind limb I/R (2.5 hours/2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…The decreases in antioxidant enzymes in sickle mouse models suggest consumption/inactivation of antioxidant enzymes by excessive reactive oxygen species in these models. This is in conformity with the observations that ischemia-reperfusion injury and increased oxidative stress (e.g., superoxide [O 2 •− ]) and hemolysis (e.g., BERK model) lead to consumption and depletion of endogenous NO and antioxidants [26].…”
Section: Effect Of Disease Severitysupporting
confidence: 90%
See 1 more Smart Citation
“…The decreases in antioxidant enzymes in sickle mouse models suggest consumption/inactivation of antioxidant enzymes by excessive reactive oxygen species in these models. This is in conformity with the observations that ischemia-reperfusion injury and increased oxidative stress (e.g., superoxide [O 2 •− ]) and hemolysis (e.g., BERK model) lead to consumption and depletion of endogenous NO and antioxidants [26].…”
Section: Effect Of Disease Severitysupporting
confidence: 90%
“…This pattern was confirmed whether using TBARS method in the presence of desferal and BHT (Figure 2A), or using using 8-isoprostane determination in the liver tissue (see Figure 2B). In BERK mice as in human SCD, chronic depletion of arginine levels, reduced NO production and NO consumption by the plasma heme as reported before [11,24,26,35] may all contribute to a proinflammatory milieu and in greater LPO levels.…”
Section: Effect Of Disease Severitymentioning
confidence: 55%
“…This results in a reduced bioavailability of nitric oxide and to vasoconstriction. 18,19 An animal study also suggested the presence L-type calcium channels on vascular smooth muscle cells, which contribute to blood flow control in an oxygensensitive manner. 20 Metabolic demands are also controlled by ATP-gated potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…al., [16] clearly indicates that alterations in production of NO and oxygen free radicals are important in the development of IRI16. As compared with treatment with L-arginine or antioxidative vitamins alone, a combination of both compounds was the best treatment against IRI, as expressed by protection against microvessel constriction, abolition of microvascular plugging, increase in NO production over the basal level, and higher blood flow.…”
Section: L-arginine and Antioxidative Vitamin Treatmentmentioning
confidence: 97%
“…The aim of the present review is to display the role of those treatments and their level of success, reporting the effective ones in reducing the extension of the injury caused by reperfusion and its aspects [1,2,3,5,6,7,8,11,12,13,15,16,17,18].…”
mentioning
confidence: 99%